Media, digital technology and learning in sport: a critical response to Hodkinson, Biesta and James - Enright, E.; Gard, M. (Physical Education and Sport Pedagogy, 2016)
Background: In their 2008 paper, Hodkinson, Biesta and James draw on the sociological theories of Pierre Bourdieu to construct what they claim is a `holistic` theoretical framework for understanding learning. While not an attempt to dissolve the long-standing opposition between `cognitive` and `situated` theories, the authors claim that thinking about learning and learners in `cultural` terms via Bourdieu's theories allows us theoretically to integrate individuals and learning contexts. The result, they claim, is a `scalable` theory of learning that overcomes the dualisms - such as structure/agency and individual/society - that dog learning theory. We welcome both Hodkinson et al.`s ideas and overall goal. However, we were struck by the absence of any mention of communications media or digital technology in their theoretical framework. Does this mean that media and digital technology can straightforwardly be mapped onto Hodkinson et al.`s theory? Or is this a serious oversight?